ANALISA PERSEDIAAN MATERIAL PADA FIRE TUBE BOILER STOCK YANG OPTIMAL DENGAN MENGGUNAKAN MARKOV CHAIN - Noorida, Titik (Department Industrial Engineering, University of Muhammadiyah Malang, 2003)
Controlling material stock becomes important problem that faced by the company because controlling it suppods production process continually. In applaying material is efforted in order getting cost of supplier more law as possible. PT. lndomaxine is one kind of company that produces tube involving two type are fre tube and water tube, in which the primary material is tube ard plat. In dealing rhe consumen needs, the company should give amount materials so that the production will be continually, and the consumer will satisfy. Having more suplies like that is caused by accepting fluctually needs, than causes less supplier optimumly and less in cost too. Based on fenomenon above, so in this research will mucstigate the methods that will be counted the number ofmaterial askhg. To determine the number of material needs decisionand to determine the cost of optimumly material, this research uses the Markov Chains method.